Curaua fibers - The queen of the fibers - Leao, Alcides Lopes [UNESP]; Cesarino, Ivana [UNESP]; Machado, Isaac Stringueta [UNESP]; Kozlowski, Ryszard M. (My University, 2017)
Nowadays, the usage of natural resources is under worldwide growing interest. From this perspective, different renewable sources have been studied to replace man-made polymers or even improve the properties of current materials. Considering these aspects, natural fibers appear as a great opportunity and among them curaua (Ananas erectifolius L. B. Smith) fiber has unique properties such as high strength, low density, high fineness and high cellulose content. In addition, due to their mechanical properties and recyclability, it has become a fiber of great interest for developing composites materials. Due to its high cellulose content, curaua fiber is an important potencial source of raw material for producing nanocellulose that can be used to manufacture nanocomposites.
Keywords: Biobased materials; Composites; Curaua; Nanofibers; Natural fibers; Natural polymers